Public Notary Services In Malaysia - Thaufiq Deen; O. Argo Victoria; Sumain Sumain (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Starting January 5, 2015 the Embassy in Kuala Lumpur requires appointments for all notarial services. Please bring your appointment confirmation sheet and arrive at the embassy 10 minutes before the appointment time. It can provide most of the same notarial services that a public notary is authorized by law to perform within the United States. Services are similary available as in U.S. and to foreign nationals with documents intended for use within the U.S. By following to the ACS Unit when requesting notary services: The documents to be notarized, including attachments, if any. The passport and one other photo identification. Witnesses, if required. (Consular staff are not alloitd to serve as witnesses.) 50.00 or the equivalent in Malaysian ringgit for each seal. Notary fees can be paid in cash or by credit card.